The 2007 global financial crisis and the Malaysian stock market: a sectoral analysis - Kassim, Salina; Abd. Majid, M. Shabri; Hamid, Zarinah (Inderscience Publishers, 2011)
The study assesses the impact of the 2007 US sub-prime crisis on the Malaysian stock market by analysing both the benchmark and sectoral indices. Specifically, it empirically examines the integration of the Malaysian, US and Japanese stock markets at the sectoral level, such as finance, manufacturing, property, industrial products and consumer products in the periods before and during the 2007 sub-prime crisis (September 2006 to May 2009). By adopting the co-integration and vector autoregressions (VAR) methods, the study documents that the nature of integration of the three markets changes due to the crisis. While there are diversification benefits in these markets at the initial stage of the crisis, there seems to be no diversification benefits in the stock markets in a prolonged ‘down market’. In a short time horizon, ‘market panic’ results in investors to withdraw funds in the crisis country and invest in other countries with calmer markets.